Changing trends of disease burden of stroke from 1990 to 2019 and its predictions among the Chinese population - Liang, Dong; Guan, Qing; Huang, Minqing; He, Yiyu; Ou, Yangjiang; Chen, Min; Zheng, Xiaoxin; Lin, Xiuquan (Frontiers in Neurology, 2023)
Objective This study aimed to understand the temporal trends in the disease burden of stroke and its attributable risk factors in China, along with the future trends in the next 25 years, that is important for effective prevention strategies and improvement, and to provide new insights into the age- and sex-specific incidence, prevalence, mortality, disability-adjusted life-years (DALYs) and their trends from 1990 to 2019, and the prediction in the next 25 years. Methods The Global Burden of Disease Study (2019) was used to extract the data on age- and sex-specific incidence, mortality, and disability-adjusted life-years (DALYs) of stroke in China, 1990–2019. We estimated the estimated annual percentage change (EAPC) to access the temporal trends of the disease burden of stroke. The R package called Nordpred was used to perform an age-period-cohort analysis to predict the prevalence of stroke. Results The number of incidence cases, deaths, and DALYs of stroke increased from 1990 to 2019. Overall downward trends were observed in the age-standardized incidence rate (ASIR) from 1990 to 2019. Significant temporal trends in mortality and DALYs of stroke were observed. High systolic blood pressure, smoking, and high-sodium diet were the main driving forces for stroke. The DALYs lost attributable to smoking were different for male and female patients. In the next 25 years, the number of new cases and deaths from stroke should continue to increase. The ASIR and age-standardized mortality rate (ASMR) should show a downward trend among male and female patients. Conclusion Despite the overall rates of stroke declined over the period from 1990 to 2019, the absolute number of people affected by stroke has substantially increased. There has been a substantial increase in the burden of stroke due to risk factors and will continue to increase in the next 25 years.